Physiological differences between sugar beet varieties susceptible, tolerant or resistant to the beet cyst nematode, Heterodera schachtii (Schmidt) under uninfested conditions - Wright, Alistair J.D.; Bussell, Jennifer S.; Stevens, Mark; Back, Matthew A.; Sparkes, Debbie L. (Elsevier, 2018)
The beet cyst nematode (BCN) is a problem to sugar beet growers around the world and can cause severe yield losses. Recently, varieties of sugar beet have been developed which are either tolerant to damage caused by BCN, or alternatively are resistant to BCN. Little is understood about these varieties and how they may have different physiological characteristics when compared with varieties of sugar beet that are susceptible to BCN. This study assessed a range of nine varieties, which were tolerant, susceptible or resistant to BCN, in pot and hydroponic tank investigations to measure differences in their canopy, early rooting and yield traits in the absence of BCN. Two field experiments, using four varieties which were susceptible, resistant or tolerant to BCN, then followed to test the hypothesis that increasing the plant population density (PPD) allows a BCN resistant variety to achieve a greater yield. In the pot and hydroponic experiments, it became clear that the varieties had different growth habits. The resistant variety yielded the least sugar and had the smallest canopy per plant. In the field experiments, which were not infested with BCN, in both years the resistant variety also showed a delayed canopy expansion compared to the other varieties. The rate of expansion could be increased by increasing the PPD. In 2016 this increased PPD resulted in higher yields of the resistant variety. However, due to better canopy development in the following year, a yield penalty was found in 2017 at higher PPDs. Understanding how different varieties need different PPDs may make resistant varieties a more economical option to cultivate in the future. However, the levels of impurities, particularly sodium impurities, in the resistant plants may still make them a less favourable choice to grow. The light tolerant varieties showed a distinct increased rooting and canopy expansion rate compared to the other variety types, while the tolerant varieties showed similar rooting and canopy traits to the susceptible varieties but had different yield responses to increased seed rate.